(untitled) (Comprehensive Journal of Science, 2025)
This study examines the transformational aspects of linguistic structures in light of the Transformational–Generative Grammar theory, which is based on the assumption that every language has basic underlying structures that rely on a deep structure representing the latent meaning in the speaker’s mind, and a surface structure manifested in the uttered forms produced by the speaker. These structures undergo various transformations that contribute to their cohesion and to the strength and clarity of their meaning. Accordingly, the study is guided by the following main questions: How is a transformed linguistic structure produced? Does the process of transformation provide a clearer and more explicit semantic value? The study adopts a descriptive–analytical approach, whereby the phenomenon of transformation is identified and classified through linguistic studies and then analyzed by focusing on linguistic structures in the Qur’anic surah, with interpretation supported by classical works of Qur’anic exegesis and grammatical analysis. The significance of this research lies in highlighting the transformational dimension and in demonstrating the semantic value of linguistic structures through processes such as fronting and postponement, addition and deletion, which are governed by the speaker’s communicative intentions.